Understanding Different Cultural Patterns or Orientations Between East and West - Qingxue, Liu (Investigationes Linguisticae, 2003)
Rudyard Kipling says in the Ballad of East and West: “East is East, and West is West; and never the twain shall meet.” Yet, he never expected that with the technological development in transportation and communication, the Westerners and Easterners that have quite different cultures respectively would meet so frequently nowadays in international settings. However, in a sense, Kipling is absolutely correct in that people with different cultural patterns (including beliefs, values, attitudes, norms, customs, and material aspects), especially those from East and West, do encounter communication difficulties, breakdowns, misunderstandings and even conflicts and confrontations just because they fail to understand each other in their intercultural communication. The study of intercultural communication is not something new. However, the perspective from which the author probes into the problematic interaction between Easterners and Westerners is something different. In the paper, the author compares some major cultural patterns: high-context communication vs. low-context communication, individualism vs. collectivism, equality vs. hierarchy, and assertiveness vs. interpersonal harmony. Each of these cultural patterns is defined by examples, two opposite patterns are contrasted, and then potential problems are presented, thus making quite obvious the differences between East and West and their possible consequences in the intercultural communication. Understanding these cultural patterns or orientations which underlie most common behavior of the Easterners and Westerners helps us to see beneath the surface to find out why people from East and West act as they do. This discovery may lead us to appreciate the rich diversity and genius that exist in different parts of the globe, avoid potential intercultural problems and become successful communicators in the interaction between East and West.